Genomic Features of Solid Tumor Patients Harboring ALK/ROS1/NTRK Gene Fusions - Dai, Yinghuan; Liu, Ping; He, Wenlong; Yang, Lizhen; Ni, Yang; Ma, Xuejiao; Du, Furong; Song, Chao; Liu, Yang; Sun, Yi (Frontiers in Oncology, 2022)
The fusions of receptor tyrosine kinase (RTK) involving anaplastic lymphoma kinase (ALK), c-ros oncogene 1 (ROS1), and neurotrophic receptor tyrosine kinase (NTRK) represent the potential targets of therapeutic intervention for various types of solid tumors. Here, the genomic features of 180 Chinese solid tumor patients with ALK, ROS1, and NTRK fusions by next generation sequencing (NGS) were comprehensively characterized, and the data from 121 patients in Memorial Sloan Kettering Cancer Center (MSKCC) database were used to compare. We found that ALK, ROS1, and NTRK fusions were more common in younger female patients (p<0.001) and showed a higher expression of programmed death ligand 1 (PD-L1). The gene-intergenic fusion and the fusion with rare formation directions accounted for a certain proportion in all samples and 62 novel fusions were discovered. Alterations in TP53 and MUC16 were common in patients with RTK fusions. The mutational signatures of patients were mainly distributed in COSMIC signature 1, 2, 3, 15 and 30, while had a higher frequency in copy number variations (CNVs) of individual genes, such as IL-7R. In the MSKCC cohort, patients with fusions and CNVs showed shorter overall survival than those with only fusions. Furthermore, the differentially mutated genes between fusion-positive and -negative patients mainly concentrated on MAPK signaling and FOXO signaling pathways. These results may provide genomic information for the personalized clinical management of solid tumor patients with ALK, ROS1, and NTRK fusions in the era of precision medicine.